Pelatihan Program Pengurangan Risiko Bencana (PRB) Melalui Pemberdayaan Masyarakat Di Daerah Rawan Bencana Kecamatan Dringu Kab. Probolinggo - Widya Addiarto; Achmad Kusyairi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The magnitude of the potential threat of flood disasters that can be repeated requires an awareness in understanding the risks of disasters that can occur. An attitude of preparedness and vigilance is needed by all levels of society, bearing in mind that losses in the form of casualties and material losses are quite large in every disaster. The main target in this service is to get a value for the level of ability to reduce disaster risk at all levels of society, awareness and how to behave in dealing with disasters. In addition, to find out how the implementation of disaster knowledge from each individual community living in disaster-prone areas. The selection of targets for this activity is based on the needs of service partners where areas are prone to repeated floods from year to year which have a broad impact on the lives of the surrounding community if attitudes and habits are not immediately improved at all levels of society. This activity is carried out by first conducting a preliminary study to determine the condition of the knowledge and attitudes of each individual community what is known about disaster management. Then after the data is obtained then training is carried out to get to increase the level of ability in disaster risk reduction, especially flood disasters. The outputs obtained are in the form of skills in disaster management such as victim evacuation and field assessment skills.